Influence of Service Quality and Marketing Mix on Customer Satisfaction and Loyalty of Padma Resort Legian - Yunita Citra Dewi; Putu Ngurah Suyatna Yasa; Ni Luh Putu Indiani (Universitas Warmadewa, 2018)
Abstract-The hospitality industry in Legian and its surroundings is experiencing a rapid development. This results in a higher competition. Padma Resort Legian is one of the hotels that is able to well maintain customers based on comparison data with hotel competitors. This study aims to determine the effect of service quality and marketing mix on customer satisfaction and loyalty at Padma Resort Legian. Research respondents are customers from overseas with a minimum age is of 17 years staying at Padma Resort Legian. The number of respondents were 100 persons, covering male and female. Data were analysed using Partial Least Square analysis (PLS version 3). The result of the study shows that service quality has no significant effect on customer loyalty; service quality has no significant effect on customer satisfaction; marketing mix has significant effect on customer loyalty; marketing mix has significant effect on customer satisfaction; and satisfaction significantly influence customer loyalty. The implication of this research is Padma Resort Legian should pay attention to the indicators of marketing mix for satisfaction increase in order to increase customer loyalty, that is by locating the marketing mix in strategic location and comfortable, spacious and comfortable hotel room. Hotel interior gives psychological comfort to the guests; the ordering and payment process is done easily; the customer gets clear information from various sources, the hotel has skilled and competent employees who are able to provide good service to the customers and the price according to the quality is received by customers. Keywords: Customer Loyalty; Customer Satisfaction; Marketing Mix; Service Quality.